Experimental dynamic analysis of composite sandwich beams with magnetorheological honeycomb core. (1st December 2018) - de Souza Eloy, Felipe; Gomes, Guilherme Ferreira; Ancelotti, Antonio Carlos; da Cunha, Sebastião Simões; Bombard, Antonio José Faria; Junqueira, Diego Morais
Highlights: Manufacturing and testing of MRE sandwich beam with CFRP composite skins and honeycomb core. Free and forced vibration tests conducted under several magnetic field intensities. The novelty on this approach refers to the use of 3D printed honeycomb core material filled by MRE. MRE sandwich beam shifted the natural frequencies due to the increase of an induced magnetic field. Abstract: This study deals with the manufacturing and testing of sandwich beams with carbon/epoxy composite skins and a honeycomb core filled with magnetorheological elastomer (MRE) in different proportions of magneto/elastomer (w/w%). Free and forced vibration tests conducted under several magnetic field intensities were performed to evaluate dynamic properties of the sandwich beams. The experimental results favorable reduction of mechanical vibrations, especially on the fundamental mode of the structure in question. We can see that MRE sandwich beam shifted the natural frequencies and amplitude of vibration due to the increase of an induced magnetic field.